The implementation of brain gym to optimize verbal communication skills in early childhood. - Tadjuddin, Nilawati; Nopriansyah, Untung (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2025)
Background : Speaking skills in early childhood are crucial for cognitive, social, and academic development. However, conventional teaching methods in Indonesian early childhood education rarely incorporate motor and neurosensory stimulation, which can limit children’s verbal abilities and self-confidence in communication. Aim : Therefore, this study aims to investigate the implementation of Brain Gym as an innovative, neuroscience-based intervention to enhance the speaking skills of young children. Method : This qualitative descriptive research was conducted at TK Khalifah Karang Anyar in South Lampung. Data were collected through observation, interviews, and documentation techniques involving children aged 5–6 years who participated in structured Brain Gym activities. Result : The findings demonstrate that Brain Gym movements such as cross crawl, lazy eight, and thinking cap significantly improved children’s verbal expression, sentence formation, and communication confidence. These activities also increased classroom engagement and effectively supported the integration of physical and linguistic development. Conclusion : This study highlights the potential of Brain Gym as a practical and playful approach to fostering early speaking skills. It contributes new empirical evidence to the field by focusing specifically on verbal development, offering valuable insights for integrating Brain Gym into early childhood curricula to promote language acquisition through movement-based learning.